2014
DOI: 10.1016/j.exppara.2014.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Maternal schistosomiasis alters costimulatory molecules expression in antigen-presenting cells from adult offspring mice

Abstract: Adult offspring of Schistosoma mansoni-infected mice showed alterations in immunity to a heterologous antigen, ovalbumin (OA). Prior breastfeeding induced increased production of anti-OA antibodies, while pregnancy impaired it. Here, we investigated the expression of costimulatory molecules on antigen-presenting cells (APCs) of the adult offspring of S. mansoni-infected mothers in response to OA. Newborn mice were divided into three groups: animals Born Infected Mothers (BIM) suckled by non-infected mothers; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Whether parasite antigens in the breast milk in contact with the suppressive intestinal mucosa microenvironment ( Weiner et al 2011) may collaborate for enhanced CD4 + FoxP3 + T-cells generation after antigenic re-exposure as adults deserve further investigations. Intriguingly, in SIM mice, we observed higher CD40 + CD80 + B-cells frequency and greater IL-2 production after OA stimulation ( Santos et al 2010, 20 , 2014 ), which are conditions to favour increased frequency of CD4 + FoxP3 + T-cells ( Zheng et al 2010) . Besides of this, the contact with anti-SEA antibodies at a young age can generate idiotypes and antiidiotypes that negatively modulate granulomatous reactions ( Caldas et al 2008) , and only passive transfer by breastfeeding, but not pregnancy, maintains the levels of anti-SEA IgG1 in the early in life ( Nóbrega et al 2012) .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Whether parasite antigens in the breast milk in contact with the suppressive intestinal mucosa microenvironment ( Weiner et al 2011) may collaborate for enhanced CD4 + FoxP3 + T-cells generation after antigenic re-exposure as adults deserve further investigations. Intriguingly, in SIM mice, we observed higher CD40 + CD80 + B-cells frequency and greater IL-2 production after OA stimulation ( Santos et al 2010, 20 , 2014 ), which are conditions to favour increased frequency of CD4 + FoxP3 + T-cells ( Zheng et al 2010) . Besides of this, the contact with anti-SEA antibodies at a young age can generate idiotypes and antiidiotypes that negatively modulate granulomatous reactions ( Caldas et al 2008) , and only passive transfer by breastfeeding, but not pregnancy, maintains the levels of anti-SEA IgG1 in the early in life ( Nóbrega et al 2012) .…”
Section: Discussionmentioning
confidence: 78%
“…Postnatal infection of animals pre-exposed to parasite antigens in utero strongly impairs both anti-OA Th1/IFN-g and Th2/IL-4 responses. Recently, we reported reduced expression of the co-stimulatory molecule CD86 in response to OA by CD11c + cells of adult animals born from infected mothers ( Santos et al 2014) that may have reduced capacity to prime anti-OA Th1 and Th2 responses.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal infection by S. mansoni can alter the degree of immune competence of the offspring in the long term, either through in-utero contact or breastfeeding. (2,3,4,5) In this study, the effects of gestation and breastfeeding were evaluated separately in S. mansoni-infected mothers. Therefore, the expression of HDACs, and cytokine production by lymphocytes and macrophages was assessed.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the immunological status of schistosomotic mothers can induce long-term alterations in the immune response of the offspring. (2,3,4,5) An experimental study on the effects of gestation and breastfeeding in infected mothers, separately, showed that gestation in these mothers led to potential immunosuppression in adult offspring, with elevated production of IL-10 and lower levels of anti-ovalbumin (OA) antibodies. (2) In addition, offspring born to infected mothers had a lower frequency of B lymphocytes, and the capacity for antigen presentation by CD11c+ cells was partially impaired.…”
mentioning
confidence: 99%
See 1 more Smart Citation